Macroeconomic Determinants of Stock Index: A Study of NEPSE - Pandey, Prakash (Economic Review of Nepal, 2020)
This research, conducted to examine the macroeconomic determinants of the stock index of Nepal, has applied the Engle-Granger cointegration to test the long-run relationship with two controlled variables—political stability index and capital mobilization through the primary market—the error correction model to determine the short-run relationship, and the Granger-causality test with lag 2 to check the causality of the variables. The data were collected from the secondary source from the years 1998 to 2020 with a sample size of n = 22 years. In the long run, broad money supply, interest rate, exchange rate, gross national income, political stability index, and capital mobilization through the primary market had statistically significant relationships with the NEPSE index; however, the relationship became positive only with the broad money supply, political stability index, and capital mobilization through primary market. Although the relationship became negative with the inflation rate, it was insignificant in the long run. In the short run, all the variables became statistically significant except for the exchange rate. The coefficient of error correction term (-1.0396) indicates that the deviation converges at the rate of 103.96% every year. The Granger-causality test showed no much stronger relationship among the variables: a unidirectional causality from broad money supply to the NEPSE index, a bidirectional causality in the case of capital mobilization through the primary market and NEPSE index, a bidirectional causality from GNI to NEPSE index, and NEPSE index not granger causing GNI.